A Pilot Study of Mothers' Breastfeeding Experiences in Infants With Cleft Lip and/or Palate. (April 2019) - Kaye, Alison; Cattaneo, Carol; Huff, Helen M.; Staggs, Vincent S.
Abstract : Background: Despite the recognized importance of human milk (HM) use, breastfeeding is often discouraged for infants with cleft lip and/or palate because of their anatomical abnormalities. Poor weight gain may require formula for calorie supplementation. Stresses associated with caring for infants with cleft lip/palate may decrease rates of HM provision to these infants. Purpose: This study investigates the experiences of mothers of infants with cleft lip/palate (CL/P) to determine choices and factors associated with providing HM to their infants. Methods: A retrospective telephone survey was administered to a cohort of mothers of infants with CL/P. Results: Fifty mothers agreed to participate in the survey. Most (78%) initiated use of HM for a median duration of 4 months, 32% provided HM for 6 months or more, and 79% exclusively expressed their HM. Poor supply was the most frequent challenge to providing HM and led to cessation in 46% of the mothers. Formula was used to supplement for poor supply or poor infant weight gain in 90% of the mothers. The best predictors of a mother's use of HM were child not in day care, genetic diagnosis, and gestational age at birth. Only 36% of mothers reported individual encouragement to provide HM, and 18% reported they were specifically discouraged from providing HM for their infants. Implications for Practice: Although initiation rates were high, there are opportunities to improve support for mothers to increase duration of HM provision in children with CL/P. Implications for Research: This study establishes a baseline for future prospective studies looking at the impact of active encouragement and provision of lactation support within the cleft team setting.